If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3a + 1) + -30 = 3(2a + 1) Reorder the terms: 3(1 + 3a) + -30 = 3(2a + 1) (1 * 3 + 3a * 3) + -30 = 3(2a + 1) (3 + 9a) + -30 = 3(2a + 1) Reorder the terms: 3 + -30 + 9a = 3(2a + 1) Combine like terms: 3 + -30 = -27 -27 + 9a = 3(2a + 1) Reorder the terms: -27 + 9a = 3(1 + 2a) -27 + 9a = (1 * 3 + 2a * 3) -27 + 9a = (3 + 6a) Solving -27 + 9a = 3 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -27 + 9a + -6a = 3 + 6a + -6a Combine like terms: 9a + -6a = 3a -27 + 3a = 3 + 6a + -6a Combine like terms: 6a + -6a = 0 -27 + 3a = 3 + 0 -27 + 3a = 3 Add '27' to each side of the equation. -27 + 27 + 3a = 3 + 27 Combine like terms: -27 + 27 = 0 0 + 3a = 3 + 27 3a = 3 + 27 Combine like terms: 3 + 27 = 30 3a = 30 Divide each side by '3'. a = 10 Simplifying a = 10
| 8x^4-28x^3+0x^2+6x-21= | | 8x-5=-12x+5 | | -11x+6=-16 | | -484-1695= | | 8x^4-28x^3+6x-21= | | c+9=-8c | | 7x-9=7+5x | | 40-4n=-4(3n-4) | | 7n+10=5n | | 4x-(9x+3)=0 | | 2/3m-1n5 | | 2x+25+1=x+17 | | 6(x-2)-6=4x | | -361-(-58)= | | 12=x+5x-6 | | -10x-4x=-7 | | (X-1)(2x-2)= | | x-.60=.54 | | A+2a+3a+4a=180 | | -17+r=-3 | | -6a-6(1+4a)=-216 | | -24-1/8p=-3/8p | | x+(x*2)=1815 | | -191+(-511)= | | R+21=21+18r | | 5m^4-5=0 | | -2y+-3z= | | -24-1/8p=-3/8 | | 2(x+15)=(3x+20) | | 9h=5+8h | | -57+(-98)= | | (2m+8)(4m-3)= |